Entrepreneurship Training Using Geodetic Global Positioning System in Vocational High School - Ishak Ishak; Ridwan Ridwan; Furqan Ali Yusuf (PT. Global Research Collaboration, 2024)
This community service program aims to improve the entrepreneurial skills of students at SMK Negeri 5 Majene through training in the use of Geodetic GPS. Although this school has shown positive development in vocational education, the entrepreneurial aspect still needs strengthening, especially in the utilization of the latest technology. The training was designed to provide students with a practical understanding of Geodetic GPS applications in business contexts, such as land mapping and area mapping management. The implementation of activities includes the preparation of training materials, workshops, and evaluation of training results. The results showed an increase in student competence in using Geodetic GPS for entrepreneurship, although there were constraints related to the availability of tools and activity schedules. This program succeeded in improving technology-based business skills among students and is expected to support them in facing an increasingly digital world of work.